Effectiveness of Tourism Management of Phuket Province - Tingga, Jaruwat; Siripornwut, Nuttawat (Journal of Management Science Nakhon Pathom Rajabhat University, 2024)
The objectives of this research were 1) to study the management and effectiveness of tourism management in Phuket province 2) to study the factors of tourism management that correlated with the tourism management effectiveness in Phuket province, and 3) to study guidelines for the development of tourism management in Phuket. The research model is qualitative research. 20 key informants were selected by purposive sampling. Use in-depth interviews. These key informants were: 4representatives from local organizations, 4 representatives from tourism agencies, 4 representatives from tour entrepreneur, 4 local people and 4 experts in tourism management and public administration academics. The study tool was structured interviews. The answer to the required information is degrading, non-participatory observation and in-depth interviews and analyze the collected data by descriptive description. Research results (1) Management conditions and effectiveness of tourism management in Phuket province, it was found that the tourism management in Phuket Province can be managed effectively (2) the tourism management factors related to the tourism management effectiveness in Phuket province and all factors contributed to the tourism management in Phuket Province. (3) guidelines for the development of tourism management in Phuket Province. The tourism program in Phuket can be done by linking many tourist attractions together should be organized in a variety in accordance with the needs of tourists and the organization of creative tourism programs to attract or persuade tourists, especially those with specific interests. Access to tourist attractions in Phuket can be done by responsible agencies that must integrate between entrepreneurs, communities, and local government organizations. Facilitate to access the resources of tourist attraction there should be a system to connect tourism between localities, provinces, and provincial groups. Access to tourist attractions must be of a standard and at a price that tourists are able to pay. Phuket attraction development can be done by presenting a distinctive identity and culture, world-class tourist attractions including cultural diversity. Arranging activities to complement travel time by creating activities during the trip when the distance between each tourist attraction if very far apart. The development of the management of tourism facilities in Phuket. This can be done by planning and implementing the development of facilities, directional and participatory tourist area and give importance to the provision of complete and modern facilities. Article history: Received 1 June 2023 Revised 25 June 2023 Accepted 26 June 2023 SIMILARITY INDEX = 4.64 %